One‐Pot Synthesis of Biheterocycles Based on Indole and Azole Scaffolds Using Tryptamines and 1, 2‐Diaza‐1, 3‐dienes as Building Blocks. Issue 19 (5th April 2016) - Mantenuto, Serena; Lucarini, Simone; De Santi, Mauro; Piersanti, Giovanni; Brandi, Giorgio; Favi, Gianfranco; Mantellini, Fabio
Abstract : The rapid and expedient assembly of three new classes of biheterocycles of biological interest, viz. indole–imidazoles4, indole–pyrroles6 and indole–triazoles8 was accomplished using different combinations of tryptamines, 1, 2‐diaza‐1, 3‐dienes, aldehydes, and/or alkynes as readily available building blocks. Twenty‐six derivatives were thus prepared in excellent yields (up to 100 %). The products were screened for in‐vitro biological studies. Some of these revealed promising anticancer activity against MCF7 and Caco‐2 human tumor cell lines. Abstract : The incorporation of indole and azole pharmacophores into new biheterocyclic scaffolds as potential anticancer agents was achieved using different combinations of tryptamines, 1.2‐diaza‐1, 3‐dienes, aldehydes, and/or alkynes as readily available building blocks.